2013
DOI: 10.1371/journal.pgen.1003505
|View full text |Cite
|
Sign up to set email alerts
|

ATM–Dependent MiR-335 Targets CtIP and Modulates the DNA Damage Response

Abstract: ATM plays a critical role in cellular responses to DNA double-strand breaks (DSBs). We describe a new ATM–mediated DSB–induced DNA damage response pathway involving microRNA (miRNA): irradiation (IR)-induced DSBs activate ATM, which leads to the downregulation of miR-335, a miRNA that targets CtIP, which is an important trigger of DNA end resection in homologous recombination repair (HRR). We demonstrate that CREB is responsible for a large portion of miR-335 expression by binding to the promoter region of miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 45 publications
0
31
0
1
Order By: Relevance
“…18 Another group showed that irradiation (IR) lead to the downregulation of miR-335 in an ATM dependent manner, and miR-335 was involved in homologous recombination repair (HRR) via suppressing CtIP expression. 24 In addition, miR15b has been established to be up-regulated following exposure to diverse stress-inducing agents, including ionizing radiation, etoposide, and hydrogen peroxide, which significantly influenced the cell cycle progression by targeting WIP1. 25 The demonstration that miR-33b-3p was dramatically downregulated when exposed to cisplatin and impacted on DDR by negative regulation of p21, further enlarged the knowledge and confirmed the effects of miRNAs on DNA damage response.…”
Section: Discussionmentioning
confidence: 99%
“…18 Another group showed that irradiation (IR) lead to the downregulation of miR-335 in an ATM dependent manner, and miR-335 was involved in homologous recombination repair (HRR) via suppressing CtIP expression. 24 In addition, miR15b has been established to be up-regulated following exposure to diverse stress-inducing agents, including ionizing radiation, etoposide, and hydrogen peroxide, which significantly influenced the cell cycle progression by targeting WIP1. 25 The demonstration that miR-33b-3p was dramatically downregulated when exposed to cisplatin and impacted on DDR by negative regulation of p21, further enlarged the knowledge and confirmed the effects of miRNAs on DNA damage response.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of checkpoint control is required for cancer initiation and development (43,44). Thus, there is a clear direct connection between miRNAs and cancer formation, which will not be discussed further in the present review.…”
Section: Signalling Cascades With Microrna Interactionmentioning
confidence: 95%
“…It has been previously reported that miR-34 may be induced by p53 and subsequently cause G1 phase cell cycle arrest (3,17), while miR-335 may be downregulated by activated ATM (43). Therefore, it appears that the genes involved in cell cycle checkpoint control are primarily Figure 1.…”
Section: Signalling Cascades With Microrna Interactionmentioning
confidence: 99%
See 2 more Smart Citations